(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article analyzes the best practices of foreign educational systems in developing the professional and personal skills of future engineering technologists. The article considers ways to improve the technical and personal skills of students through innovative teaching methods, practice-based education and international cooperation. Based on foreign experience, the importance of developing professional skills, improving personal and social skills in the training of future engineering technologists is emphasized. It also discusses how these experiences can be implemented in the education system of Uzbekistan, and foreign experience is shown as an important factor in training specialists ready for professional activity.